Utilizing Effective Communication in Interactions with Same-Age Peers: Children Aged 4-5 Years - Murni, Sri; Desmita, Desmita; Kharisma Diyenti, Adella; Silvianetri, Silvianetri; Buddike, W Dinesh (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
The use of effective communication by young children aged 4-5 years in interactions with peers is very important because it has a very influential impact on the social development and communication skills of children. The aim of this research is to determine the use of effective communication by young children aged 4-5 years in interactions with peers. This research method uses qualitative methods with observation, interviews and documentation methods. The results of this research show that the use of effective communication by young children aged 4-5 years in interactions with peers is very important due to the social development and communication skills of children. From this research it can be concluded that the use of effective communication by young children aged 4-5 years in interactions with peers is very important for social development as well as training social skills in children and children being able to control their own emotions. Therefore, the researcher hopes that future researchers will further develop the use of effective communication from young children aged 4-5 years in interactions with peers. The researcher also recommends to future researchers to use this research as a reference in conducting research on the use of effective communication in early childhood 4-5 years old in interactions with peers.┬á┬á